MDA-5 recognition of a murine norovirus. - Stephen A McCartney (Public Library of Science (PLoS), 2008)
Noroviruses are important human pathogens responsible for most cases of viral epidemic gastroenteritis worldwide. Murine norovirus-1 (MNV-1) is one of several murine noroviruses isolated from research mouse facilities and has been used as a model of human norovirus infection. MNV-1 infection has been shown to require components of innate and adaptive immunity for clearance; however, the initial host protein that recognizes MNV-1 infection is unknown. Because noroviruses are RNA viruses, we investigated whether MDA5 and TLR3, cellular sensors that recognize dsRNA, are important for the host response to MNV-1. We demonstrate that MDA5-/- dendritic cells(DC) have a defect in cytokine response to MNV-1. In addition, MNV-1 replicates to higher levels in MDA5-/- DCs as well as in MDA5-/- mice in vivo. Interestingly, TLR3-/- DCs do not have a defect in vitro, but TLR3-/- mice have a slight increase in viral titers. This is the first demonstration of an innate immune sensor for norovirus and shows that MDA5 is required for the control of MNV-1 infection. Knowledge of the host response to MNV-1 may provide keys for prevention and treatment of the human disease.